Hubungan Kualitas Tidur Karyawan Terhadap Produktivitas Kerja di Lingkungan Rumah Sakit TPT Dr. R. Soeharsono Banjarmasin - Muhammad Robby; Puji Ayu Asri Sri Lestari; Muhammad Oldyanoor (CV. ITTC INDONESIA, 2025)
Sleep quality is an important aspect in daily life, especially for employees who work in a hospital environment. Hospitals are places that demand a high level of awareness and focus from their staff to ensure optimal health services to patients. Therefore, understanding how sleep quality affects the work productivity of health workers is very important. The aim of the research was to analyze the relationship between employee sleep quality and work productivity in the TPT Dr Hospital environment. R. Soeharsono Banjarmasin. This research is a quantitative research with a cross-sectional approach using the chi square test. The location of this research is Dr. R. Soeharsono Banjarmasin. The population and sample used in this study were 15 people including medical personnel (doctors, nurses) and non-medical personnel (administration, technicians). The instrument in this study used a questionnaire. The research results show that sleep quality has a significant relationship with employee work productivity at TPT Dr. Hospital. R. Soeharsono Banjarmasin. Of the 6 respondents with poor sleep quality, 5 of them had poor work productivity. Meanwhile, of the 9 respondents with good sleep quality, 7 had good work productivity. Chi-Square test results show p-value = 0.041, which means there is a significant relationship between sleep quality and work productivity. The conclusion from this research is that there is a relationship between employee sleep quality and work productivity in the TPT Dr. Hospital Environment. R. Soeharsono Banjarmasin.